Macroeconomics - Dornbusch, Rudiger (McGraw-Hill, 2001)
"Macroeconomics" has been a long-standing, leading intermediate macroeconomic theory text since its introduction in 1978. This revision retains most of the texts traditional features, including a middle-of-the-road approach and contemporary research, while updating and simplifying the exposition.